Observing the LMC with APEX: signatures of large-scale feedback in the molecular clouds of 30 Doradus - Grishunin, Konstantin; Weiss, A.; Colombo, D.; Chevance, Mélanie; Chen, C.-H. R.; Güsten, R.; Rubio, M.; Hunt, L. K.; Wyrowski, F.; Harrington, K.; Menten, K. M.; Herrera-Camus, R. (Astronomy and astrophysics, 2024)
Context: Stellar feedback plays a crucial role in star formation and the life cycle of molecular clouds. The intense star formation region 30 Doradus, which is located in the Large Magellanic Cloud (LMC), is a unique target for detailed investigation of stellar feedback owing to the proximity of the hosting galaxy and modern observational capabilities that together allow us to resolve individual molecular clouds - nurseries of star formation. Aims: We study the impact of large-scale feedback on the molecular gas using the new observational data in the 12CO(3 − 2) line obtained with the APEX telescope. Methods: Our data cover an unprecedented area of 13.8 sq. deg. of the LMC disc with a spatial resolution of 5 pc and provide an unbiased view of the molecular clouds in the galaxy. Using these data, we located molecular clouds in the disc of the galaxy, estimated their properties, such as the areal number density, relative velocity and separation, width of the line profile, CO line luminosity, size, and virial mass, and compared these properties of the clouds of 30 Doradus with those in the rest of the LMC disc. Results: We find that, compared with the rest of the observed molecular clouds in the LMC disc, those in 30 Doradus show the highest areal number density; they are spatially more clustered, they move faster with respect to each other, and they feature larger linewidths. In parallel, we do not find statistically significant differences in such properties as the CO line luminosity, size, and virial mass between the clouds of 30 Doradus and the rest of the observed field.Conclusions. We interpret our results as signatures of gas dispersal and fragmentation due to high-energy large-scale feedback.
Gesehen am 11.09.2024